2015
DOI: 10.1007/s00125-015-3724-3
|View full text |Cite
|
Sign up to set email alerts
|

Haploinsufficiency of interferon regulatory factor 4 strongly protects against autoimmune diabetes in NOD mice

Abstract: Aims/hypothesis: Interferon regulatory factor (IRF)4 plays a critical role in lymphoid development and the regulation of immune responses. Genetic deletion of IRF4 has been shown to suppress autoimmune disease in several mouse models, but its role in autoimmune diabetes in NOD mice remains unknown. Methods:To address the role of IRF4 in the pathogenesis of autoimmune diabetes in NOD mice, we generated IRF4-knockout NOD mice and investigated the impact of the genetic deletion of IRF4 on diabetes, insulitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Tissue Sections (3 Îźm) were stained with H&E (Servicebio, Wuhan, China) or processed for staining for insulin (GB11334, Servicebio). Insulitis was scored on the basis of islet infiltration with the following grades: grade 0, no insulitis or peri-insulitis; grade 1, insulitis involving < 25% islet; grade 2, insulitis involving 25–50% islet; grade 3, insulitis involving 50–75% islet, and grade 4, insulitis involving > 75% and/or complete islet infiltration (Akazawa et al 2015 ). More than 100 islets were scored in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Tissue Sections (3 Îźm) were stained with H&E (Servicebio, Wuhan, China) or processed for staining for insulin (GB11334, Servicebio). Insulitis was scored on the basis of islet infiltration with the following grades: grade 0, no insulitis or peri-insulitis; grade 1, insulitis involving < 25% islet; grade 2, insulitis involving 25–50% islet; grade 3, insulitis involving 50–75% islet, and grade 4, insulitis involving > 75% and/or complete islet infiltration (Akazawa et al 2015 ). More than 100 islets were scored in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Mice deficient in IRF4 expression fail to develop fully functional Tmem, and lack of IRF4 expression results in Tex ( 265 , 266 ). Strikingly, NOD mice deficient in IRF4 fail to develop T1D and show dysfunctional T cell responses ( 267 ). Maintenance of long-lived Tmem responses has been tied to the pro-memory transcription factor TCF1 ( 268 – 270 ).…”
Section: The Role Of T Cell Receptor Signaling In the Maintenance Of mentioning
confidence: 99%
“…As type 1 diabetes is considered to be a T‐cell‐mediated disease, 19 we analyzed the T cell composition in PLNs from Smad4 tKO and WT NOD mice at 12 weeks of age. We found that the size and total cell number of PLNs were increased in Smad4 tKO compared with WT NOD mice (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%